STRATEGI PENGEMBANGAN KOGNITIF ANAK USIA DINI DI TK ISLAM AL- ITTIFAQIAH - windira, winta; Muharrahman; Triyana (Program Studi Pendidikan Islam Anak Usia Dini, 2024)
Early childhood cognitive development is an important aspect of education that influences children's future intellectual and emotional abilities. This research uses a descriptive qualitative method which aims to provide an in-depth picture of early childhood cognitive development strategies at the Al-Ittifaqiah Islamic Kindergarten. This approach was chosen because it allows to explore and understand complex phenomena contextually and in detail. Early childhood cognitive development strategies at Al-Ittifaqiah Islamic Kindergarten emphasize a holistic approach that combines Islamic values ​​with modern learning methods. This research aims to evaluate the effectiveness of the cognitive development strategies implemented at the Al-Ittifaqiah Islamic Kindergarten.